The end of alchemy money, banking, and the future of the global economy - King, Mervyn A. (New York W. W. Norton & Company, 2016)
Something is wrong with our banking system. We all sense that, but Mervyn King knows it firsthand; his ten years at the helm of the Bank of England, including at the height of the financial crisis, revealed profound truths about the mechanisms of our capitalist society. In The End of Alchemy he offers us an essential work about the history and future of money and banking, the keys to modern finance.
Includes bibliographical references (pages 371-417) and index.
Keywords: Capitalism